Fracture resistance of roots enlarged with various rotary systems and obturated with different sealers - Selen İnce Yusufoglu; Melek Akman; Makbule Bilge Akbulut; Ayce Ünverdi Eldeniz (Tabriz University of Medical Sciences, 2019)
Background. This in vitro study compared the fracture resistance of roots instrumented either with ProTaper or One Shape rotary systems and filled with one of the silicate, epoxy resin or silicone-based sealers. Methods. Sixty single-rooted extracted mandibular premolars were decoronated to a length of 13 mm and then randomly divided into two main groups (n=30) in terms of the rotary system used for preparation. Group 1 samples were instrumented with the ProTaper Universal system up to a master apical file of #F2, while samples in group 2 were enlarged with One Shape system. The two main groups were then divided into 3 subgroups in terms of the sealer used (n=10) and filled with guttapercha (either F2 or MM-GP points) of the rotary system used and one of the sealers as follows: group 1, BioRoot RCS + ProTaper F2 gutta-percha; group 2, AH Plus + ProTaper F2 gutta-percha; group 3, GuttaFlow + ProTaper F2 gutta-percha; group 4, BioRoot RCS+ MM-GP points; group 5, AH Plus + MM-GP points; and group 6, GuttaFlow + MM-GP points. Each specimen then underwent fracture testing by using a universal testing machine at a crosshead speed of 1.0 mm/min until the root fractured. Data were statistically analyzed. Results. Two-way ANOVA showed no significant differences between the groups. One Shape instruments showed significantly better fracture resistance compared to ProTaper instruments. Statistically, no significant difference was found between AHPlus, GuttaFlow and BioRoot RCS sealers. Conclusion. It can be concluded that the rotary system used for the instrumentation of teeth has some influence on the fracture resistance, while the root canal sealers do not have such an effect.